Simultaneous electricity and bacterial nanocellulose (BNC) production from mature coconut water (MCW) waste - Yodrach, Rachchanon; Rattanabundan, Purita; Chaijak, Pimprapa (Brawijaya University, 2025)
Mature coconut water (MCW) is a by-product of various coconut industries. It is produced in large quantities annually. If untreated, this waste can pollute groundwater systems upon discharge. In this study, MCW was used as a low-cost medium for bacterial nanocellulose (BNC) production. The effects of exogenous carbon and nitrogen sources were studied under static conditions. Suitable conditions were then selected for use in a microbial fuel cell (MFC) to generate electrical energy from BNC fermentation. Subsequently, the BNC was immobilized with silver nanoparticles (AgNPs) and used against the pathogenic bacteria Escherichia coli and Staphylococcus aureus. The results showed that the system generated maximum current density (CD) and power density (PD) of 54.250 ± 0.180 mA/m² and 5.886 ± 0.039 mW/m², respectively. The AgNPs-immobilized BNC film effectively inhibited the growth of both Gram-negative E. coli and Gram-positive S. aureus with inhibition zones measuring 26.0 ± 0.3 mm and 30.1 ± 0.2 mm, respectively. This study provides new insights into producing electrical energy during BNC synthesis fermentation.